Ракушковые рачки (Crustacea, Ostracoda) бассейна р. Десны и ее притоков - Голубничая, Л.В. (Вестник зоологии, 1969)
Data are presented on occurrence of 23 species of Ostracoda in the Desna basin, its tributaries and their floodplain reservoirs. Morphological description is given of Noto-dromas persica, found for the first time in the fauna of the USSR. The observations are presented on the morphology, ecology and spreading of Candonopsis kingsleii, Candoda marchica and Cypris subglobosa.